Implementasi Pemantauan dan Evaluasi Penggunaan Dana Hibah Rehablitasi Dan Rekonstruksi di Kabupaten Agam Tahun 2022 - Febriansyah, Nugraha; Pandoyo, Pandoyo (Reformasi Administrasi, 2025)
Agam Regency is one of the areas with high disaster intensity which has implications for both material and non-material losses so that post-disaster rehabilitation and reconstruction are needed in Agam Regency. The problem in this study is that the management of grant funds in Agam Regency has not been managed properly. The purpose of this study is to determine the monitoring and evaluation of the Implementation of the Use of Rehabilitation and Reconstruction Grant Funds in Agam Regency in 2022. The theory used in this study is Dunn's evaluation theory which includes planning, implementation, and reporting. The method used in this study is qualitative with a case study approach. The data analysis technique used in this study refers to Cresswell & cresswell (2018) which consists of several processes, namely Organize and prepare the data for analysis, Read or look at all the data, Start coding all of the data, Generate a description and themes, Representing the description and themes, and interpretation. The results of the study found that monitoring and evaluation of the Use of Rehabilitation and Reconstruction Grant Funds in Agam Regency in 2022 through planning, implementation, and reporting. The results of the implementation of the use of grant funds cannot be implemented optimally due to the limited time given in the use of grant funds. Supporting and inhibiting factors in policy implementation consist of internal and external factors. The recommendation of this study is the need for strengthening commitment from stakeholders, strengthening cross-sector coordination, and increasing transparency and accountability